RISK FACTORS OF ANGULAR CHEILITIS AT GUSTI HASAN AMAN DENTAL HOSPITAL SOUTH KALIMANTAN - Aulia Azizah; Selviana Rizky Pramitha; Maharani Laillyza Apriasari (Dentino : Jurnal Kedokteran Gigi, 2021)
Background: The second highest burden of all diseases in world population includes infectious disease with a total of 28% cases. Angular cheilitis is an infectious condition on the corner of the mouth that may initiate masticatory, facial expression and speech dysfunction due to the involvement of orbicularis oris muscle surrounding the lips. The management of angular cheilitis comprises the elimination of causative microbes using antifungal agent. Therapeutic failure reveals the disregard of any related risk factor. Purpose: To analyze the risk factors of angular cheilitis in Gusti Hasan Aman Dental Hospital year 2019. Method: This study resorted analytical descriptive design of quantitative approach using cross-sectional method. Samples were 65 dental statuses of patients in Oral Medicine Clinic of Gusti Hasan Aman Dental Hospital year 2019. Result: Univariate data analysis presented the distribution of children category aged ≤ 18 years old (75.8%), men (54.8%), not consuming vegetable and fruit behaviour (46.8%), duration of treatment 1-7 days (56.4%), and incidence of angular cheilitis (75.8%). Fisher exact test unveiled the relationship between age and angular cheilitis (p<0.05) in which age ≤ 18 years old was 4.266 fold higher to experience angular cheilitis, while the relationship between gender and angular cheilitis (p<0.05) demonstrates the predilection of male with 4.853 fold at risk than female. Conclusion: Age and gender are risk factors in the incidence of angular cheilitis at Gusti Hasan Aman Dental Hospital year 2019.  Keywords : Age, Angular Cheilitis, Behavior, Gender